Management and Adaptation in Crisis Situations Across Different Generations in Bangkok Based on the PESTEL Framework - Watcharodomprasert, Vutti (Journal of Humanities and Social Sciences Thonburi University, 2024)
This research aims to 1) study different age groups in each age range regarding management and adaptation during crises using the PESTEL framework, and 2) analyze the factors within each dimension of PESTEL that affect management capabilities and crisis adaptation. The research employs a quantitative research design. The population for this study consists of residents of Bangkok, with a sample size of 385 people, divided into Baby Boomers (98 people), Generation X (111 people), Generation Y (105 people), and Generation Z (71 people). The study's findings indicate that different age groups have varying capabilities in managing and adapting during crises. A comparison of the average crisis management capabilities among the different age groups shows that Baby Boomers have significantly different average adaptation capabilities compared to the other three groups. Regarding the analysis of the regression equations of independent variables with crisis management, four factors were found to be relevant: political factors, economic factors, environmental factors, and legal factors. When analyzing the regression equations of independent variables with crisis adaptation, four factors were identified: political factors, economic factors, social factors, and legal factors.